News and Analysis : Bridging the divide. (24th October 2017) - Tesh, Sarah
Abstract: The recent International Conference on Women in Physics shows that there is still a long way to go to reach gender equality. Sarah Tesh reports from Birmingham, UK – where education activist Malala Yousafzai made a surprise appearance